2017
DOI: 10.1007/s10586-017-0958-5
|View full text |Cite
|
Sign up to set email alerts
|

Collecting large training dataset of actual facial images from facebook for developing a weighted bagging gender classifier

Abstract: Many of previous gender classifiers have a common problem of low accuracy in classifying actual facial images taken in real environments since they were learned in restricted environments. Therefore, this study proposes to swiftly collect uncontrolled actual facial images from Facebook to construct training dataset and proposes a weighted bagging gender classifier which utilizes a Facebook dataset to increase the classification accuracy. In the proposed gender classification scheme, utilization of unique featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Earlier studies showed that LBP and Gabor jets offer better performance than raw pixels when used with SVM and variants. For this reason, these two features are extensively used in the literature [15,[26][27][28][29][30][31].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies showed that LBP and Gabor jets offer better performance than raw pixels when used with SVM and variants. For this reason, these two features are extensively used in the literature [15,[26][27][28][29][30][31].…”
Section: Related Workmentioning
confidence: 99%
“…The bagging method for gender recognition is studied in [27,30]. In [27], multiple SVM based linear models are used to create bagging of classifiers and stacking for gender recognition.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation